A highly flexible form-stable silicone-octadecane PCM composite for heat harvesting - Soo, Debbie Xiang Yun (2023)
Phase Change Materials (PCM) are efficient materials for thermal management and energy storage due to its high latent heat and recyclability. Many strategies have been employed to form stabilize PCMs through their phase transition; however these materials are almost invariably rigid. Herein a novel flexible form-stable PCM composite was successfully prepared by physical mixing and low temperature curing. They were well characterized in terms of various techniques including X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), mechanical and leakage test, etc. A leakage test showed that the composite with 50% octadecane loading was form-stable with only 2.44% leakage. From the differential scanning calorimetry (DSC) results, the octadecane/silicone (Oct/Si) composite was found to possess a latent heat of 103.8 J/g, and an upshift in phase transition temperature was also observed from octadecane's melting point of 30.3 °C to between 34.4 and 37.8 °C, probably due to thermal insulation or microencapsulation by the silicone matrix. Thermogravimetric analysis (TGA) data supported its good thermal stability within this temperature range and mechanical testing of the composites further confirmed its flexibility and durability as evidenced by the Young's Modulus at 388.92 kPa and elongation at 341.42%, making Oct/Si composites useful for application in areas of temperature regulation, cooling, energy harvesting and wearable devices.